Analysis of Fieldwork Practice Management for Improving Students’ Work Readiness - Yuda Prasetia; Widiyanti Widiyanti; Yoto Yoto (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Nahdlatul Wathan Mataram, 2025)
This study aims to analyze the management of the Field Work Practice Program at one vocational high school in Trenggalek and its impact on students’ work-readiness. This study employed a qualitative method, with in-depth interviews as the primary data collection technique. Data were analyzed using an interactive model consisting of data collection, data reduction, data presentation, and conclusion drawing. The research findings indicate that the Field Work Practice program was implemented using a Block Release system over a six-month period during the sixth semester. The implementation stages consisted of a pre-Field Work Practice phase encompassing socialization, briefing, and registration; a core phase involving student placement with business or industry partners, accompanied by regular monitoring; and a post-Field Work Practice phase covering student withdrawal, examination implementation, report preparation, and certificate issuance. The Field Work Practice program was shown to make a positive contribution to the development of students’ technical skills, discipline, communication abilities, and understanding of workplace culture. Nevertheless, several challenges remain, including misalignment between the school curriculum and industry needs, as well as differences in the competency levels of teachers and students, particularly in terms of soft skills. Overall, the Field Work Practice program significantly enhanced graduates’ work-readiness, though continuous improvement is still needed to optimize outcomes